The intellectual structure of sustainability accounting in the corporate environment: A literature review - Ahmad Kalbouneh; Khaled Aburisheh; Loona Shaheen; Qasem Aldabbas (Cogent Business & Management, 2023)
The paper focuses on a current study on sustainable accounting as well as potential future research issues. 679 publications dealing with sustainable accounting produced between 2003 and 2022 were assessed using a bibliometric and visualization tool for the Web of Science cor collection database and viewer-based literature. The study looks at cluster analysis, all-keyword co-occurrence analysis, and bibliographic coupling mapping. This study allows us to suggest future research directions that may be beneficial in reflecting on the major influence that technology will have on the expansion of sustainable accounting in a business. The survey identified four major research trends in accounting for sustainability: reporting and disclosure, sustainability as part of management control systems, accounting and environmental management, stakeholder involvement and accountability, sustainability and business social responsibility. Education and Information Sharing About Sustainable Accounting, Green Sustainable Accounting, Technology Usage in Sustainable Accounting, Including AI, Big Data, and IoT, and ESG: Sustainable Accounting. This report presents a thorough examination of research trends in the intersection of sustainable accounting, as well as prospective research directions.
Keywords: 650; bibliographic-coupling analysis; bibliometric analysis; keywords analysis; Sustainability accounting; Web of Science